Quality control in non-staple food markets: Evidence from India - Fafchamps, Marcel; Hill, Ruth Vargas; Minten, Bart (International Food Policy Research Institute, 2007)
Using original data collected about growers, traders, processors, markets, and village communities, we compare the situation in four states – Tamil Nadu, Uttar Pradesh, Maharashtra, and Orissa. We examine the way that information about crop attributes is conveyed (or not) along the value chain. We also document the infrastructure available at the level of the market. We find that little information circulates about unobservable crop characteristics. Growers receive a price premium when they dry, grade, and pack their produce, but we find no evidence that information about crop health and safety or agricultural practices circulates through the value chain or that growers are encouraged to follow specific agricultural practices for quality purposes. Market infrastructure is deficient regarding sanitation, with few public toilets, inadequate drainage, and no coordinated pest control.